2016
DOI: 10.1017/s1751731116000495
|View full text |Cite
|
Sign up to set email alerts
|

Review: Milking robot utilization, a successful precision livestock farming evolution

Abstract: Automatic milking systems (AMS), one of the earliest precision livestock farming developments, have revolutionized dairy farming around the world. While robots control the milking process, there have also been numerous changes to how the whole farm system is managed. Milking is no longer performed in defined sessions; rather, the cow can now choose when to be milked in AMS, allowing milking to be distributed throughout a 24 h period. Despite this ability, there has been little attention given to milking robot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
40
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 40 publications
4
40
0
1
Order By: Relevance
“…In our study, higher pasture nutritional values were observed compared with those reported by McEvoy et al (2008), Bargo et al (2002) and Pérez-Prieto et al (2011), promoting higher pasture intake and lower grass to concentrate substitution rate. The negative MR observed in May presumed a low substitution rate and could be explained by the high WSC content of spring pasture promoting increase in pasture intake and in MY, which is in accordance with other authors (Peyraud and Delagarde, 2013;John et al, 2016).…”
Section: Impact On Voluntary Cow Trafficsupporting
confidence: 91%
See 3 more Smart Citations
“…In our study, higher pasture nutritional values were observed compared with those reported by McEvoy et al (2008), Bargo et al (2002) and Pérez-Prieto et al (2011), promoting higher pasture intake and lower grass to concentrate substitution rate. The negative MR observed in May presumed a low substitution rate and could be explained by the high WSC content of spring pasture promoting increase in pasture intake and in MY, which is in accordance with other authors (Peyraud and Delagarde, 2013;John et al, 2016).…”
Section: Impact On Voluntary Cow Trafficsupporting
confidence: 91%
“…The cause of the higher frequency of night visits in May is unclear. Weather conditions influenced milking and refusal schedules, with a reduction of robot visitations to the robot during hot period (1200 to 1600 h) in July and August with visit schedules moving to periods 1600 to 0000 h. This observation is in accordance with other studies ( Ketelaar-de Lauwere et al, 2000;John et al, 2016). Although the majority of milkings (56% in LC and 50% in HC) occurred within periods of new pasture allocation corresponding to changing gates (from 0800 to 1200 h and from 1600 to 2000 h), HC came more regularly to the robot than LC.…”
Section: Impact On Voluntary Cow Trafficsupporting
confidence: 91%
See 2 more Smart Citations
“…Simulation-optimisation based on animal behaviour was developed for robotic milking farms at the beginning of this century (Halachmi, 2004). In this PLF issue, John et al (2016) review the utilisation of robots after a farm was designed and a robot operated. They also review the robot milking-pasture combination.…”
mentioning
confidence: 99%